2022
DOI: 10.1108/itse-05-2022-0057
|View full text |Cite
|
Sign up to set email alerts
|

Students’ achievement in an online course on technical writing and communication skills

Abstract: Purpose This study aims to investigate students’ satisfaction, self-efficacy and perceived competencies in a ‘technical writing and communication skills’ course after the switch of teaching the course from face to face to fully online during and after COVID-19. The study also measured the Achievement of Accreditation Board for Engineering and Technology course learning outcomes (CLOs). Design/methodology/approach A descriptive cross-sectional survey design approach was adopted in this study. Students were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…The researchers also attributed a large number of respondents' dissatisfaction with online education to poor organization and design of online learning activities, difficulties in maintaining interaction and comprehending online materials when using the Moodle platform, infrastructure issues, professors' insufficient skills in online teaching, a lack of regular feedback about their progress from their instructors, and a limited number of resources that a student could access. These results coincide with those found in several studies [37,39,40,[46][47][48][49]. On the other hand, the research conducted by Khan et al [41] emphasizes the positive influence of the design of online courses on students' satisfaction, performance, knowledge, and skills.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The researchers also attributed a large number of respondents' dissatisfaction with online education to poor organization and design of online learning activities, difficulties in maintaining interaction and comprehending online materials when using the Moodle platform, infrastructure issues, professors' insufficient skills in online teaching, a lack of regular feedback about their progress from their instructors, and a limited number of resources that a student could access. These results coincide with those found in several studies [37,39,40,[46][47][48][49]. On the other hand, the research conducted by Khan et al [41] emphasizes the positive influence of the design of online courses on students' satisfaction, performance, knowledge, and skills.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, the research conducted by Khan et al [41] emphasizes the positive influence of the design of online courses on students' satisfaction, performance, knowledge, and skills. Besides, Gopal et al [35] and Yasin et al [49] agreed that in order to improve the effectiveness of online teaching, instructors should prioritize self-efficacy when designing online courses. The participants' low attitudes toward their asynchronous classes were consistent with the findings of previous studies, such as the research conducted by Borg [50], who found that students reported higher levels of comfort using online synchronous classes than both in-person and online asynchronous classes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By doing so, learners, instructional institutions, and employers can get entry to applicable records each time and anywhere. With a stronger credit management system in place, the liquidity of recognition results can be significantly improved [5].…”
Section: The Susceptible Liquidity Of Focus Effects Can Be Attributed...mentioning
confidence: 99%